DIVERSIFIKASI SEBAGAI SALAH SATU PILAR KETAHANAN PANGAN (Forum Penelitian Agro Ekonomi, 2017)
Global financial crisis and climate changes have affected food security in a more vulnerable situation. Food security pillars, in this respect should be strengthened.  The food security pillar should not rely only on quantitative approaches, but also on other pillars in a wider food spectrum. One of the feasible ways to enhance food security is to develop food diversification based on local food commodities. This paper is aimed to assess some vulnerable points of national food security, the significant of the diversification to enhance food availability and its prospect as one of the pillars to develop steady food security in Indonesia.
Keywords: food security; diversification; local food commodity; ketahanan pangan; diversifikasi; bahan pangan lokal